Experimental Evolution Reveals Redox State Modulates Mycobacterial Pathogenicity - Jiang, Zheng; Zhuang, Zengfang; Mi, Kaixia (Frontiers in Genetics, 2022)
Understanding how Mycobacterium tuberculosis has evolved into a professional pathogen is helpful in studying its pathogenesis and for designing vaccines. We investigated how the evolutionary adaptation of M. smegmatis mc251 to an important clinical stressor H2O2 allows bacteria to undergo coordinated genetic mutations, resulting in increased pathogenicity. Whole-genome sequencing identified a mutation site in the fur gene, which caused increased expression of katG. Using a Wayne dormancy model, mc251 showed a growth advantage over its parental strain mc2155 in recovering from dormancy under anaerobic conditions. Meanwhile, the high level of KatG in mc251 was accompanied by a low level of ATP, which meant that mc251 is at a low respiratory level. Additionally, the redox-related protein Rv1996 showed different phenotypes in different specific redox states in M. smegmatis mc2155 and mc251, M. bovis BCG, and M. tuberculosis mc27000. In conclusion, our study shows that the same gene presents different phenotypes under different physiological conditions. This may partly explain why M. smegmatis and M. tuberculosis have similar virulence factors and signaling transduction systems such as two-component systems and sigma factors, but due to the different redox states in the corresponding bacteria, M. smegmatis is a nonpathogen, while M. tuberculosis is a pathogen. As mc251 overcomes its shortcomings of rapid removal, it can potentially be developed as a vaccine vector.